Teaching free speech across the communication studies curriculum. Issue 1 (3rd July 2018) - Dewberry, David R.; Burnette, Ann; Fox, Rebekah; Arneson, Pat
ABSTRACT: While we applaud the efforts of those instructors who teach classes in free speech, we recognize that as a discipline we are often missing important opportunities to teach students about free speech in a variety of other communication studies courses. Our discipline and our democracy rest on the tenets of free speech, and our classrooms should reflect its importance. In this essay, we outline how topics in free speech can be integrated into four different types of classes in the communication curriculum that do not focus solely on the First Amendment.